مسلم ملک میں غیر مسلم حکمران کا تقرر:مسلمان مفکرین کی آرااور منتخب مسلم ممالک کے دساتیر کی روشنی میں ایک مطالعہAppointment of Non-Muslim Ruler in a Muslim Country: A Study in the light of the Opinions of Muslim Thinkers and Selected Constitutions of Muslim Countries (Al-Qamar, 2021)
The modern world has turned in to multicultural and the socio-political form. Changes have created a new code of conduct at a global level not just socioly but politically as well. Multireligious societies have evolved due to which the nature of modern politics has raised new questions for traditional Muslim thoughts. It has been said that Muslim countries have also to choose a new democratic system of politics in which it is not inevitable to appoint only Muslim rulers in Muslim states. Traditional and liberal narratives have got into the ideological conflict in Muslim countries in this regard. This study deals with the logic of both above-said categories of thinkers. The shreds of evidence from the Quran and Hadith, which prohibits the appointment of non-Muslim in Muslim countries, are presented first along with the logics put forward by such Muslim scholars who take them into consideration. Inferences of the liberal narrative have been explained followed by ending remarks through conclusion.
Keywords: Islam; Politics; Ruler; Khalifa; President; Muslim; Non-Muslim; Liberal; Tradition